The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/plphys/kiac569
|View full text |Cite
|
Sign up to set email alerts
|

Kinase CIPK9 integrates glucose and abscisic acid signaling to regulate seed oil metabolism in rapeseed

Abstract: Rapeseed (Brassica napus), an important oil crop worldwide, provides large amounts of lipids for human requirements. Calcineurin B-like (CBL)-interacting protein kinase 9 (CIPK9) was reported to regulate seed oil content in plant. Here, we generated gene-silenced lines through RNA interference biotechnology and loss-of-function mutant bnacipk9 using CRISPR/Cas9 to further study BnaCIPK9 functions in seed oil metabolism of rapeseeds. We discovered that compared with wild type (WT) lines, gene-silenced and bnaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…In A. thaliana, AtCIPK9 regulates K + homeostasis in a K + -deficient environment [44]. VvCIPK9 from grape can improve salt tolerance in transgenic tobacco, and BnaCIPK9 regulates oil metabolism in oilseed rape [45]. We found that, compared with WT, BrrCIPK9.1-overexpressing plants showed a greater root length under alkaline (pH 8.5) stress, indicating that they were better adapted to this stressor.…”
Section: Discussionmentioning
confidence: 72%
“…In A. thaliana, AtCIPK9 regulates K + homeostasis in a K + -deficient environment [44]. VvCIPK9 from grape can improve salt tolerance in transgenic tobacco, and BnaCIPK9 regulates oil metabolism in oilseed rape [45]. We found that, compared with WT, BrrCIPK9.1-overexpressing plants showed a greater root length under alkaline (pH 8.5) stress, indicating that they were better adapted to this stressor.…”
Section: Discussionmentioning
confidence: 72%
“…Arabidopsis seeds with the cbl2/3rf mutation displayed reduced size, weight, and fatty acid content when compared to the wild-type seeds [ 51 ]. B-like (CBL)-interacting protein kinase 9 ( CIPK9 ) of Brassica napus was reported to regulate seed oil content, and both rapeseed knock-out lines and gene-silenced lines showed decreased levels of polyunsaturated fatty acids [ 52 ]. SGK2 is responsible for encoding a ribosomal protein S6-like protein that is localized in the plastids, and by map-based cloning, it was revealed that the Arabidopsis rfc (regulator of fatty acid composition) 3 gene can alter the fatty acid composition of membrane lipids, resulting in an increase in oleic acid (18:1) levels and a decrease in α-linolenic acid (18:3) levels among total fatty acids [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PUFA content of seeds is mainly reduced by knocking out FAD genes (Jiang et al, 2017;Morineau et al, 2017;Okuzaki et al, 2018;Huang et al, 2020;Jarvis et al, 2021;Lee et al, 2021;Liu et al, 2022;Shi et al, 2022). Another study successfully decreased the PUFA content by knocking out CIPK9 genes (Wang et al, 2023). In B. napus it was shown that FAD genes are highly expressed in pollen, thus explaining the high levels of PUFAs (Piffanelli et al, 1997).…”
Section: Decreased Amounts Of Pufa Can Negatively Affect the Health O...mentioning
confidence: 99%
“…Changes in oil composition can therefore affect plant communication, signalling pathways and plant resistance to biotic or abiotic stressors (Kawall, 2021). In addition, there are further NGT applications with altered plant composition which could be relevant to interactions with pollinators, e. g. traits with a significant impact on hormone signalling (Sun et al, 2018;Wang et al, 2023) or flavonoid content (Xie et al, 2020;Zhai et al, 2020). In addition, changes in oil composition may also have effects on various other species which feed on plants, such as pest insects (Hixson et al, 2016) or other wild species (Colombo et al, 2018).…”
Section: Further Observations Regarding Changes In Oil Compositionmentioning
confidence: 99%